Basics of Algorithms Intelligent System - Yu, Rusyaeva E.; Poltavsky, A.V.; Ahobagze, G.N. (2019 International Multi-Conference on Industrial Engineering and Modern Technologies (FarEastCon), 2019)
It is shown that the fundamental basis and the primary basis for the concepts in the field of algorithmization of modern intelligent systems lie in the philosophical knowledge of the world and the process of thinking as such. It is indicated that the creation of modern artificial intelligent systems is based primarily on the knowledge of the actual thinking of the person, his ability to create different ways, mechanisms, tools of intellectual activity. It is emphasized that algorithms are practically the first among them and have now become one of the main ways of building intelligent systems. It is stated that the theory of algorithms itself, as one of the basic and fundamental branches of mathematics, transforming in its time from philosophy, is based on studies of epistemology, the subject of which is the process of human knowledge as such, in its entirety. It is presented from the position of epistemology and ontology as fundamental sections for the philosophy that the creation of modern integrated modules of information technology systems is unthinkable without taking into account the complex of relationships, interactions in the system "man-machine", and algorithms are the leading way to develop any artificial systems, including intelligent systems. Science is an important area of human activity, always aimed at the development and systematization of objective knowledge about the real world.